Recent advancement and strategy on bio-hydrogen production from photosynthetic microalgae. (November 2019) - Anwar, Muhammad; Lou, Sulin; Chen, Liu; Li, Hui; Hu, Zhangli
Highlights: Recent advancement on genetic and metabolic engineering overcome hydrogen production limitations. The potential of micro RNA regulation in bio-hydrogen production is critically analyzed. Fermentative hydrogen production from microalgal biomass is presented. Economics assessment of bio-hydrogen production is discussed. Abstract: Recently, ensuring energy security is a key challenge to political and economic strength in the world. Bio-hydrogen production from microalgae is the promising alternative source for potential renewable and self-sustainability energy but still in the initial phase of development. Practically and sustainability of microalgae hydrogen production is still debatable. The genetic engineering and metabolic pathway engineering of hydrogenase and nitrogenase play a key role to enhance hydrogen production. Microalgae have photosynthetic efficiency and synthesize huge carbohydrate biomass, used as 4th generation feedstock to generate bio-hydrogen. Recent genetically modified strains of microalgae are the attractive source for enhancing bio-hydrogen production in the future. The potential of hydrogen production from microRNAs are gaining great interest of researcher. The main objective of this review is attentive discussed recent approaches on new molecular genetics engineering and metabolic pathway developments, modern photo-bioreactors efficiency, economic assessment, limitations and knowledge gap of bio-hydrogen production from microalgae.